A MULTIVARIATE TAPHONOMIC APPROACH TO UNDERSTANDING MIDDEN FORMATION IN THULE INUIT CONTEXTS: A CASE STUDY FROM ARCTIC CANADA - Porawski, Tom (Scholarship@Western, 2008)
Archaeologists attempting to reconstruct local and regional Thule subsistence behaviour place great emphasis on faunal assemblages recovered from Thule semisubterranean house structures and their associated middens (refuse dumps). Despite the importance of this dataset, limited attention has been given to understanding the taphonomic processes that created these assemblages. The faunal material observed in middens can be highly variable due to the impact of natural and cultural formation processes. This thesis uses faunal data collected from a Thule site (NeHd-1, ca. AD 1400-1600) located near Hall Beach, Nunavut to examine the formation and preservation of three different middens. Application of a multivariate taphonomic approach indicates that formation processes played an important role in determining the nature of these samples, affecting each deposit differently. A better understanding of this variability provides the basis for more informed inferences regarding human behaviour at both the intra- and inter-site level.